2003
DOI: 10.1159/000071294
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Renal Impairment and Sodium Imbalance in Patients Undergoing Transjugular Intrahepatic Portosystemic Shunting for the Prevention of Variceal Rebleeding

Abstract: Background/Aim: Kidney function and portal pressure have prognostic relevance in nonshunted patients with cirrhosis. Since insertion of a transjugular intrahepatic portosystemic shunt (TIPS) reduces portal pressure and may improve the renal function, the aim of the present study was to investigate the prognostic role of renal impairment and portal hemodynamics in patients with compensated cirrhosis electively shunted due to recurrent variceal hemorrhages. Methods: Data of 101 consecutive and prospectively foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…This was not unexpected, since MELD was originally designed to predict mortality after TIPS [14]. Contrarily to other studies [3,18,19], in our population sodium level and creatinine were not independently associated with mortality. This may be due to the clinical protocols applied in our Hospital, which include the routine infusion of human albumin in cirrhotic patients with refractory ascites [20] leading to a significant improvement of renal function.…”
Section: Discussionsupporting
confidence: 65%
“…This was not unexpected, since MELD was originally designed to predict mortality after TIPS [14]. Contrarily to other studies [3,18,19], in our population sodium level and creatinine were not independently associated with mortality. This may be due to the clinical protocols applied in our Hospital, which include the routine infusion of human albumin in cirrhotic patients with refractory ascites [20] leading to a significant improvement of renal function.…”
Section: Discussionsupporting
confidence: 65%
“…Renal failure is a frequent complication of advanced cirrhosis [1] due to several causes [3], and is associated with a high mortality [4,[14][15][16]. Furthermore, a pre-transplant renal impairment affects post-transplant survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TIPS can improve type II hepatorenal syndrome [8]. However, these data are contrary to other studies which demonstrate that a high serum creatinine is a powerful predictor of a poor outcome after TIPS [9]. It is therefore prudent at this time to reserve TIPS for those with refractory ascites and a serum creatinine !2 mg/dl.…”
Section: See Article Pages 990-996mentioning
confidence: 94%